THE SENTENCE CONNECTORS IN ACADEMIC INDONESIAN AND ENGLISH - Yassir Nasanius (Linguistik Indonesia, 2013)
Sentence connectors are a well-recognized feature of academic English. There is, however, little research on sentence connectors that has been undertaken in academic Indonesian. The present study attempted to establish whether sentence connectors in academic Indonesian are as common as those in academic English. As many as nine articles published in Linguistik Indonesia in 2009 were used as samples and were examined to determine the occurrences of sentence connectors in academic Indonesian. The results of the study indicated that sentence connectors in academic Indonesian were as common as those in academic English. In fact, the writers of academic Indonesian tended to use sentence connectors more frequently than their counterparts in English. That is, Swales and Feak (2004) found that on average over two sentence connectors occurred in every page of academic text written in English, while the present research found that on average over five sentence connectors occurred in every page of academic texts written in Indonesian.